A transformação social de uma ferramenta potencialmente estratégica no contexto organizacional - Cardoso, Eros Renato Silva (2015)
Taken from the viewpoint of Social Construction (SC), aligned with the field of Practice-Based Studies (PBS) focusing on the strategy-as-practice approach, it is possible to note that organizational strategies may interfere with the social context of an o